Efficacy of combined androgen blockade therapy in patients with metastatic hormone‐sensitive prostate cancer stratified by tumor burden. (25th January 2022) - Nagumo, Yoshiyuki; Onozawa, Mizuki; Kojima, Takahiro; Terada, Naoki; Shiota, Masaki; Mitsuzuka, Koji; Yasumoto, Hiroaki; Matsumoto, Hiroaki; Enokida, Hideki; Sugiyama, Takayuki; Kuroiwa, Kentaro; Saito, Toshihiro; et al.
Abstract : Objective: To determine the effect of combined androgen blockade with a first‐generation anti‐androgen on the prognoses of metastatic hormone‐sensitive prostate cancer patients stratified by tumor burden. Methods: We retrospectively analyzed the cases of metastatic hormone‐sensitive prostate cancer patients who were treated with androgen deprivation therapy in 2008–2017 at 30 institutions in Japan. To compare the overall survival and progression‐free survival rates of the patients treated with castration monotherapy and combined androgen blockade, we carried out a Cox proportional hazards regression analysis using both inverse probability of treatment weighting and instrumental variables methods. High‐burden disease was defined as the presence of four or more bone metastases and/or visceral metastasis. Results: Of 2048 patients, 702 (34.3%) and 1346 (65.7%) patients were classified as the low‐ and high‐burden groups, respectively. In each group, >80% of the patients were treated with combined androgen blockade. Although there was no significant between‐group difference in the overall survival according to the androgen deprivation therapy method, in the high‐burden group the progression‐free survival of the combined androgen blockade‐treated patients was significantly better than that of patients treated with castration monotherapy: inverse probability of treatment weighting method, hazard ratio 0.49, 95% confidence interval 0.34–0.71; instrumental variables method, hazard ratio 0.80, 95% confidence interval 0.60–0.98. Conclusion: In the high‐burden group, combined androgen blockade with a first‐generation anti‐androgen resulted in superior progression‐free survival compared with castration monotherapy. For well‐selected metastatic hormone‐sensitive prostate cancer patients, the use of combined androgen blockade might still have some suitable scenarios.